The effect of using the hypoxic training mask in developing some physiological variables and physical abilities of Kirkuk Cycle sport team –youth - Talib Hamadi, Firas (International Journal of Psychosocial Rehabilitation, 2020)
According to the researcher's experience, he noticed that there are weaknesses in Kirkuk clubs and teams in some physical abilities, especially speed and strength endurance , and because the game needs these two elements, we, as researchers, had to enter into this research problem and our use of this type of aid device due to the lack of studies that dealt with the use of modern aids that are not familiar to our trainers and to develop and improve the training process and physical abilities of riders. A training mask in a training curriculum to develop some physical and physiological indicators for the reach of accurate scientific results that can be used in the future and then raise the level of Kirkuk players in particular and Iraq in general to the highest levels and competition at the international level. The researcher used the experimental approach to its relevance to the nature and problem of the research, and the researcher conducted the exploratory experiment and the pre- and post-tests and applied the training method, and the researcher used the statistical bag to extract the results, and the researcher concluded through his research that the training mask had an effective role in reducing the parts of oxygen atoms in the air for the respiratory process during the exercises and led the player to hypoxia.